(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2016)
The technique of performance assessment in 2013 in curriculum 2013 is used to assess students’ ability to do something. This assessment technique is in line with the aim and the characteristics of biology subject at Madrasah Aliyah level. As a branch of science, biology has three aspects which i.e. process, product and attitude. Biology learning is led to reach those three aspects. The use of performance assessment technique is in line with the process aspect in which the Biology learning demands students to do scientific performance as a part of learning process. Scientific performance will lead students to learn how Biological knowledge is acquired. So the development of performance assessment instruments is really important to be mastered by the teachers of Biology. This is being more strengthen by a compulsory assessment on basic competence related to the skill domain as recommended by 2013 curriculum. The steps on developing assessment instrument starts from deciding the skill that will be assessed to the developing observation formand performance assessment rubric is presented on this paper. This article also discuss the position of performance assessment based some experts opinions.